TTB Protects Astrocytes Against Oxygen-Glucose Deprivation/Reoxygenation-Induced Injury via Activation of Nrf2/HO-1 Signaling Pathway - Liu, Liang; Zhao, Zhichen; Yin, Qimeng; Zhang, Xiaolu (Frontiers in Pharmacology, 2019)
Neonatal hypoxic/ischemic encephalopathy (NHIE) is a severe condition that leads to death or neurological disability in newborns. The underlying pathological mechanisms are unclear, and developing the target neuroprotective strategies are urgent. 2,7,2′-trihydroxy-4,4′7′-trimethoxy-1,1′-biphenanthrene (TTB) is a natural product isolated from Cremastra appendiculata (D. Don) Makino and Liparis nervosa (Thunb.) Lindl. TTB has demonstrated potent cytotoxic activity against stomach (HGC-27) and colon (HT-29) cancer cell lines. However, none of the studies have addressed the effects of TTB in NHIE. In the present study, an oxygen-glucose deprivation/reoxygenation (OGD/R)-induced astrocyte injury model was established to investigate the effect of TTB and its potential mechanisms. Our results showed that TTB alleviated the OGD/R-induced reactive oxygen species increase and the intracellular antioxidant capacity of superoxide dismutase activity decrease. Moreover, TTB potentially prolonged the activation state of the nuclear factor erythroid 2-related factor 2 (Nrf2)/heme oxygenase-1 (HO-1) pathway and maintained the protection against oxidative stress in OGD/R-induced astrocytes by inducing the nuclear translocation and up-regulation of Nrf2 along with the enhanced expression of the downstream target gene HO-1. Furthermore, TTB treatment diminished the accumulation of hypoxia-inducible factor-1α (HIF-1α) and vascular endothelial growth factor (VEGF) expression induced by OGD/R. We also found TTB-treated astrocytes reversed the inhibition of OGD/R on neurite growth of neurons by the astrocyte-neuron coculture system. In conclusion, TTB inhibited the OGD/R-induced astrocyte oxidative stress at least partially through the inhibition of HIF-1α and VEGF via the Nrf2/HO-1 signaling pathway.